Production and reproduction performances of Diara buffaloes in the Gangetic basin of Bihar - CHANDRAN, P C; PANDIAN, S JEGAVEERA; DEY, A; KAMAL, REENA; KUMARI, RAJNI (The Indian Journal of Animal Sciences, 2015)
Morphometric and body weight traits studied in the present investigation indicate that Diara buffaloes are medium-sized animals with prominent forehead and loosely curved horns. They are smaller than the heavy-sized breeds like Murrah, Jaffarabadi and Nili-Ravi. The height, length and girth of female Diara buffaloes were 94.96±0.58 cm, 92.96±0.49 cm and 115.93±0.81 cm up to 1 year of age and 133.60±0.69 cm, 138.36±0.74 cm and 200.79±0.95 cm above 7 years of age, respectively. Estimated adult body weights of Diara buffaloes pooled over ages were found to be 494.99±27.15 kg in males and 483.21±3.58 kg in females. Diara buffaloes are good milkers with an average per day milk production was found to be 7.8 litre and peak yield reached up to 10.5 litre per day. Diara population remains so far largely untouched and breed improvement programmes, probably involving selective breeding, could be undertaken to further enhance the genetic potential of these buffaloes.